Political dynamics in organizational identity breach and reconstruction: findings from the crisis in UNICEF Germany - Jacobs, CD; Kreutzer, K; Vaara, E (Academy of Management, 2020)
This paper elucidates the political dynamics of organizational identity breach and reconstruc-tion. Drawing on the revealing case of UNICEF Germany, we develop a process model of four phases of identity breach and reconstruction: build-up of identity tensions, revelation of identi-ty breach, identity reconstruction, and enactment of the reconstructed identity. Our analysis explains how each phase was characterized by specific political strategies employed by the managerialist and idealist organizational members, the effects of these strategies on the power balance and consensus/conflict over organizational identity, and how particular triggers explain shifts from one phase to another. By so doing, our analysis advances our understanding of or-ganizational identity breach and reconstruction as political processes and paves the way for new studies of political identity dynamics in other contexts.